Analysis of Collateral Risk Mitigation Without Collateral Rights at PT. Permodalan Nasional Madani Branch Office Jakarta - Cahya Putra, Mohamad Hendry; Agus Salim (Dinasti International Journal of Digital Business Management, 2023)
This study aims to analyze the implementation of strategic risk management activities for non-mortgage guarantees, analyze risk management that occurs if a guarantee is not installed with mortgage rights in it and analyze the executor's efforts if there is bad or problematic financing at PT. Permodalan Nasional Madani Branch Office Jakarta. Researchers used a type of field research (field research), with a qualitative approach, using data obtained directly from employees PT. Permodalan Nasional Madani Branch Office Jakarta. Data was collected by means of interviews, observation and documentation. Data validity analysis used source triangulation, data analysis used data reduction, data presentation and conclusion. Identification and measurement of non-mortgage credit risk is carried out by PNM before extending credit to prospective customers. PNM conducts assessments, surveys of customer backgrounds, businesses and guarantees provided by customers. Monitoring and controlling credit risk is carried out when credit has been given to customers. Steps taken include persuasive billing and visits to troubled customers.